PENGARUH DIVIDEN TERHADAP NILAI PERUSAHAAN YANG DIMODERASIKAN DENGAN KUALITAS AUDIT - Dea Tiara Monalisa Butar-Butar; Stefy (Universitas Katolik Indonesia Atma Jaya, 2023)
Dividend is the main factor which impact value of a company. The study is to seek outcome on dividends to company value via audit quality as moderating variable and other control variables such as profitability, cash holdings, debt level and Firm Size in IDX30 companies starting in 2018-2022. The main reason for the firm being audited by big four KAP as the quality of the audit opinion is believed to be higher than non-big four KAP. Therefore, researcher is interested in examining the outturn of dividend on company’s value, with audit quality as moderation. Data is collected by non purposive sampling. The analysis used multiple linear regression. The results of the f test show that dividends have a simultaneous effect on firm value. The outcome of the analysis show dividend is significant positive on firm value without being moderated by audit quality. The R2, 0.615433, which explains that the dividend has an effect of 61.54% to firm value and the rest 38.46% is influenced by variables beyond the study. The author suggests adding variables and also using the Tobins'q proxy to be compared with Price to Book Value (PBV) as material for consideration for further research.